(untitled) (Altre Modernità, 2016)
This paper focuses on the topic of censorship associated with the use of strong language and swear words in the translation of contemporary American TV series. In AVT, more specifically in Italian dubbing, the practice of censorship, in the form of suppression or toning down of what might be perceived as offensive, disturbing, too explicit or inconvenient, still remains a problematic issue. By focusing on two recent successful TV series - Girls and Orange is the New Black – which are characterized by the use of strong language (swear words, politically incorrect references) and the presence of taboo subjects (homosexuality, sex, drugs, violence) – this study will consider the different translation choices applied in dubbing and fansubbing. Previous academic studies have underlined the fact that professional translators tend to remove, more or less consciously, the disturbing elements from the source text, while fansubbers try to adhere as much as possible to the original text, not only in terms of linguistic contents but also in terms of register and style. The results of this analysis seem on the one hand to confirm that there is still not a systematic set of rules that govern the translation of strong language in dubbing, and on the other to indicate that the gap between professional and amateur translation is perhaps becoming less pronounced.